Bimbingan Teknis, Fasilitas dan Insentif Terhadap Kinerja Bhayangkara Pembina Keamanan dan Ketertiban Masyarakat Kepolisian Resor Deli Serdang - Arnis Syafni Yanti; Syaiful Bahri; Amini Amini (Jurnal Manajemen dan Bisnis, 2020)
The purpose of this research is to know the influence of technical guidance, facilities and incentives to performance Bhabinkamtibmas Polres Deli Serdang. The population in this study was the entire personnel of the Bhabinkamtibmas Polres Deli Serdang amounting to 230 people. The sample is used as many as 40 personnel Bhabinkamtibmas who are the rank of Bripka. The data collection techniques in this study are documentation and questionnaire list. Data analysis techniques using multiple linear regression analyses, classical assumption Test T, Test f and coefficient of determination. Data processing in this study uses the program SPSS 22.00 for Windows Software. Based on the results of the research conducted, from a partial test of guidance to significant impact on performance. Partial testing of facilities has significant effect on performance. Incentive partial testing has significant effect on performance. Simultaneous testing of the influence of technical guidance, facilities and incentives has significant effect on performance.